The origin of coarse garnet peridotites in cratonic lithosphere: New data on xenoliths from the Udachnaya kimberlite, central Siberia - Doucet, Luc-Serge; Ionov, D.; Golovin, A. (Springer, 2013)
We report new textural and chemical data for 10 garnet peridotite xenoliths from the Udachnaya kimberlite and examine them together with recent data on another 21 xenoliths from the 80-220 km depth range. The samples are very fresh (LOI near zero), modally homogeneous and large ( > 100 g). Some coarse-grained peridotites show incipient stages of deformation with < 10 % neoblasts at grain boundaries of coarse olivine. Such microstructures can only be recognized in very fresh rocks, because fine-grained interstitial olivine is strongly affected by alteration, and may have been overlooked in previous studies of altered peridotite xenoliths in the Siberian and other cratons. Some of the garnet peridotites are similar in composition to low-opx Udachnaya spinel harzburgites (previously interpreted as pristine melt extraction residues), but the majority show post-melting enrichments in Fe and Ti. The least metasomatized coarse peridotites were formed by 30-38 % of polybaric fractional melting between 7 and 4 GPa and =1-3 GPa. Our data together with experimental results suggest that garnet in these rocks, as well as in some other cratonic peridotites elsewhere, may be a residual mineral, which has survived partial melting together with olivine and opx. Many coarse and all deformed garnet peridotites from Udachnaya underwent modal metasomatism through interaction of the melting residues with Fe-, Al-, Si-, Ti-, REE-rich melts, which precipitated cpx, less commonly additional garnet. The xenoliths define a complex geotherm probably affected by thermal perturbations shortly before the intrusion of the host kimberlite magmas. The deformation in the lower lithosphere may be linked to metasomatism. © 2013 Springer-Verlag Berlin Heidelberg.